The Appreciative System of Urban ICT Policies - Galit Cohen; Peter Nijkamp (Tinbergen Institute, 2003)
Information and Communication Technologies (ICT) have become important tools topromote and realize a variety of public goals and policies. The growing importance of ICT indaily life, business activities and govemance prompts the need to consider the role of ICTmore explicitIy in urban administrations and policies. What are the city maker's expectationsabout ICT? And how do they assess the future implications of ICT for their city? An analysisof these questions is needed to provide us with a better understanding of the extent to whichurban authorities are willing to invest in and to adopt ICT policy. This paper offers both aconceptual and an operational model that aims to map out the causes and implications of ICTperceptions and views of urban policy makers and/or administrative officials (denoted asurban front liners ). This is folIowed by the presentation of an operational path model, viz. alinear structural equations model (Lisrel). The model serves to describe and test therelationships between perceptions of the city, policy makers' beliefs about ICT and theassociated urban ICT policy. According to the model, respondents that perceive their city ashaving many urban functions (e.g., commercial centre, service centre, higher educationcentre) have more awareness to various ICT tools and are likely to consider a multiplicity ofICT measures as relevant to their city. Respondents that consider their city as having severebottlenecks (e.g., traffic congestion, housing shortage) are less likely to think of ICTmeasures and ICT -related goals as relevant to their city, nor that the municipality impactssignificantly on ICT in the city. Furthermore, respondents that perceive their city as sufferingfrom many socio-economic problems (unemployment, ageing population, industrial declineand so on), are likely to consider many ICT tools as relevant to their city, although they havea low awareness of the specific tools to be deployed. Finally, respondents who believe thatICT will affect significantIy (and positively) the city and its administration, tend to attach ahigh municipal influence on ICT, and consider many ICT initiatives as relevant to their city.
Keywords: R00; 330; ICT; perceptions; Lisrel model; urban decision-makers; Informationstechnik; Kommunalpolitik